Die Nachwirkungen des fehlgeschlagenen Erdnuß-Projekts in Ostafrika - Jätzold, Ralph (ERDKUNDE, 1965)
The East-African Groundnut Scheme, started with a large basic capital and high hopes in 1946, was in 1950 abandonned mainly for the reasons that costs of clearing had turned out up to ten times higher while the yields per acre had come to only half of what been estimated. Despite having failed as such the Groundnut Scheme nevertheless has left remarkable consequences. Late in 1950 it was modified into an experimental undertaking charged with the task of investigating the economic practicability of clearing and of mechanized large scale agriculture and the possibility of settling the area cleared so far (ca. 175,000 acres). Early in 1955 the direction of this undertaking passed to a national body, the Tanganyika Agricultural Corporation (abbrev. TAC). The experiences gained in its settlement schemes have been applied in formulating the new agricultural policy of the Tanganyika government which plans to overcome the backward subsistence economy of many parts of the country by a substantial villagisation programme. The TAC has transformed the three areas of the former Groundnut Scheme i. e. Kongwa, Urambo and Nachingwea into flourishing, partly even exemplary agricultural regions. Kongwa, situated in the thorny savannah of the Central Province, has become a large cattle breeding area; apart from a central ranch of the TAC there are 150 african settlers attached to the former, each with a heard of 20-30 cattle. Urambo in the west, situated in the Miombo forest at 1,100 m. altitude, has become a tobacco growing area with about 20 larger and 1278 smaller tobacco farms. Owing to its success this settlement scheme is being copied in other parts of the country of a similar physical nature. Only in Nachingwea in the south, lying in a more humid variant of the Miombo forest at 400 m. altitude, there is as yet no proper agricultural cash product. Eleven mechanized estates of the TAC and about 170 small farms of Africans carry out mixed agriculture with soyabeans and groundnuts as main crops. The TAC plans there to give in the future increased emphasis to cattle breeding. Cattle farming has appeared as a new economic element; owing to having been infested by the Tsetse fly cattle farming could previously not be practised in the south-east of Tanganyika. It was not possible to preserve all improvements of the infrastructure brought about in connexion with the Ground nut Scheme. The two new railway lines for instance were not paying their way and have been dismantled. However, the new roads and the harbour of Mtwara in the south, constructed for the anticipated groundnut export, continue to function and exert a favourable influence on the economic development of the region.